Analysis of integrated uses of dockless bike sharing and ridesourcing with metros: A case study of Shanghai, China. (July 2022) - Liu, Xinghua; Fan, Jing; Li, Ye; Shao, Xuan; Lai, Ziliang
Highlights: Characteristics of integrated uses of ridesourcing and DBS with metros are studied. Integrated DBS and ridesourcing trips are concentrated in different areas. Proportion gap between two modes reaches a peak in distance interval of 0–0.5 km. The most travel time of integrated trips is within 14 min. The built environment has different impacts on the two integrated uses. Abstract: To enhance the last-mile connectivity of metros, transport managers are experimenting with the integration of shared mobility modes, such as dockless bike sharing (DBS) and ridesourcing. To provide theoretical guidance for transport managers, it is imperative to deepen knowledge of the differences between the integration of DBS and ridesourcing with metros. A three-level structure was developed in this study to identify integrated DBS and ridesourcing trips using observed data from DiDi and Mobike in Shanghai, China. The travel characteristics of two identified integrated shared mobility modes were then compared. Finally, negative binomial regression models were built to investigate the factors influencing these two integrated uses. Comparative analysis shows that the travel distance intervals with the highest proportions are 0.5–1.0 km for DBS and 1.0–1.5 km for ridesourcing. In terms of temporal distribution, morning peaks of integrated DBS trips are higher and earlier than those of ridesourcing. In the spatial dimension, integrated DBS and ridesourcing trips are mainly concentrated in the central urban area and suburban areas, respectively. Further examination indicates that the built environment has different impacts on these two integrated uses. These results provide an improved understanding of the seamless integration of shared mobility modes with metros.